Assessment of Striga resistance in wild relatives of sorghum under field condition - Gamar, Yasir Ahmed (Journal of Agricultural Sciences (Belgrade), 2019)
The witch-weeds (Striga spp) are destructive root parasites of many crops. They results in considerable crop damage especially, in the semiarid-tropic parts of the world. The parasite control is difficult due to the complexity of the parasite life cycle, and the large number of seeds produced by the parasite with prolongs viability. The most promising way of controlling the parasite is through the development of the resistant crop cultivars. Identification of different sources of resistance will enhance breeding for resistant varieties. Wild relatives of sorghum are rich with genetic diversity and have a broad genetic base including novel and valuable traits like Striga and disease resistance. In this context, 55 wild sorghum lines were collected from three regions of Sudan including Eastern (Gadaref), Central (Gezira), and Western (North Kordofan). The collected germplasm was assessed for Striga resistance using artificial infestation. The results showed significant difference in number of Striga emerged plants compared to the checks. Hence, significant difference was showed in number of days to 50% plants to reach flowering, plant height, and grain yield per hectare. The wild relatives were also morphologically characterized and the result showed the 55 lines structured in six groups independently from their geographical regions.